Innovations during the Covid‐19 pandemic to maintain delivery of care for vocal cord dysfunction (VCD) in a multidisciplinary team (MDT) clinic. Issue 8 (4th May 2022) - Koh, Joo; Baxter, Malcolm; Phyland, Debra; Ruane, Laurence; Avram, Adriana; Leahy, Elizabeth; Lau, Kenneth; MacDonald, Martin; Leong, Paul; Bardin, Philip
Abstract : See related Reply